Economic Impacts of Minimum Wage Policy Adjustments in Indonesia: A Panel Analysis of Provincial Data - Imam Safei Muslim (Journal of Applied Econometric, 2026)
Background:This study investigates the economic impacts of minimum wage policy adjustments across Indonesian provinces using panel data from 2010 to 2023. The research aims to explore how changes in minimum wage at the provincial level affect key economic indicators, such as employment rates, GDP growth, poverty levels, and income inequality.Objective:The objective of this research is to empirically assess the effects of provincial minimum wage changes on economic indicators. The focus is on understanding how these adjustments impact employment, economic growth, and social outcomes in Indonesia.Method:The study employs fixed-effects panel regression models with provincial and time dimensions. It controls for province-specific heterogeneity and common time shocks, analyzing 34 provinces over 14 years (2010-2023), totaling 476 province-year observations. This methodology is used to identify the causal effects of minimum wage changes on the selected economic indicators.Findings and Implications:The findings indicate nuanced effects of minimum wage increases. Formal sector employment shows a modest negative impact (elasticity of −0.15), especially in labor-intensive manufacturing sectors, while informal sector employment rises by 0.23% for each 10% wage increase. GDP growth is positively correlated with minimum wage levels (elasticity of 0.08), suggesting that wage-driven consumption outweighs competitiveness concerns.Conclusion:This study provides rigorous province-level evidence from Indonesia’s diverse economic landscape, demonstrating the importance of understanding the broader macroeconomic context in shaping the effectiveness of labor policies like minimum wage adjustments. Policymakers must optimize these frameworks to ensure balanced economic growth, poverty reduction, and reduced income inequality across provinces.